Improved System for Smart City Street-Lighting Controlling based on Web Technology Principles - Saeed, Rezgar Hasan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The world’s electricity consumption predominantly relies on non-renewable energy sources. Prior to implementing these comprehensive modifications, it is imperative to actively seek for chances to economize and optimize its utilization. Modern cities are progressively adopting the concept of smart cities, with smart energy being a key focus area. Smart energy is one of the components of smart cities that cities have incorporated. In this context, a sophisticated control system employing fuzzy logic is suggested for the purpose of regulating street lighting in a manner that ensures it operates solely when required. The purpose of this is to dynamically regulate the brightness of the lights based on the traffic conditions on the street and adaptively in real-time. This helps minimize potential harm to the eyes of the driver or pedestrians when the lights are switched on or off. The proposed lighting system allowed for a significant reduction in energy usage through efficient and intelligent means. To assess how well the suggested controller performed, three test scenarios were run. Variations in roadway lengths, vehicle counts, and vehicle speeds were present in the first, second, and third scenarios. Comparing the suggested controller’s performance to that of the controllers employed in the use case was the aim. MATLAB software has been utilized for the design and simulation of the system under examination. The simulation results indicate that the suggested fuzzy controller is more advantageous for implementing smart city street lighting on lengthy roadways with a high concentration of traffic.